Analysis and Control Design for a Class of Fractional Order Time-Delay Systems - BOUDANA, Marwa; LADACI, Samir; LOISEAU, Jean Jacques (Algerian Journal of Signals and Systems, 2020)
In this paper, we consider a class of fractional order time-delay systems and propose a fractional order control design for their stabilization. The controller parameter’s adjustment is achieved in two steps: first, the relay approach is used to compute satisfactory classical PID coefficients, namely kp, Ti and Td. Then, the fractional orders ʎ and µ are optimized using performance criteria. Simulation results show the efficiency of the proposed design technique and its ability to enhance the PID control performance.